2019
DOI: 10.3390/biology8040072
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Propagation of Rheophytic Orchid, Epipactis flava Seidenf.—A Comparison of Semi-Solid, Continuous Immersion and Temporary Immersion Systems

Abstract: Epipactis flava Seidenf. is an endangered Thai rheophytic orchid that has recently shown a rapid decrease in its natural habitat, prompting an urgent need for conservation using ex situ reintroduction methods. Temporary immersion system (TIS) has been successfully applied for large-scale propagation in various plants species. Propagation efficiency of E. flava using TIS was investigated and compared with conventional semi-solid system (SSS) and liquid continuous immersion system (CIS). The highest percentage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The level of camptothecin (2.5 mg/g DW) of Camptotheca acuminata grown in TIS was comparable to the semi-solid culture [106]. In contrast, plumbagin, as the main bioactive compound from Drosera communis, was reduced in its yield by TIS compared to the semi-solid system and continuous immersion system [69]. Shoots of Lycium barbarum propagated in TIS were characterized by high concentration of total phenolic (23.6 mg gallic acid equivalent-GAE/g DW) and low flavonoid content (1.9 mg rutin equivalent-RE/g DW) compared to semi-solid culture [107].…”
Section: Culture System and Bioactive Compounds Contentmentioning
confidence: 82%
See 1 more Smart Citation
“…The level of camptothecin (2.5 mg/g DW) of Camptotheca acuminata grown in TIS was comparable to the semi-solid culture [106]. In contrast, plumbagin, as the main bioactive compound from Drosera communis, was reduced in its yield by TIS compared to the semi-solid system and continuous immersion system [69]. Shoots of Lycium barbarum propagated in TIS were characterized by high concentration of total phenolic (23.6 mg gallic acid equivalent-GAE/g DW) and low flavonoid content (1.9 mg rutin equivalent-RE/g DW) compared to semi-solid culture [107].…”
Section: Culture System and Bioactive Compounds Contentmentioning
confidence: 82%
“…The comparison of three different culture systems showed the prevalence of TIS over conventional semi-solid and liquid continuous immersion to induce the highest shoot number (1.5) of Epipactis flava [69] and to obtain the largest FW (3109.0 g) and DW (351.8 g) of Lessertia frutescens [79]. In addition, the application of TIS treatments on Hippeastrum × chmielii yielded greater propagation rates (6.44) than semi-solid medium (3.85) [75].…”
Section: Culture System and Biomass Productionmentioning
confidence: 99%
“…ex Andrews the highest number of leaves was obtained in a temporary immersion bioreactor (BIT®) and automated temporary immersion container (RITA®) compared to GIB (Ramírez-Mosqueda and Iglesias-Andreu 2016). Also, in Epipactis ava Seidenf seedlings there are reports of a greater number of leaves in the temporary immersion system (TIS) than with the semi-solid medium and with the continuous immersion system (Kunakhonnuruk et al 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Asymbiotic seed germination is a promising propagation tool for mass-multiplication and conservation of rare and threatened orchid species (Arditti 2008). This technique has successfully been used to rescue several species including Paphiopedilum wardii (Zeng et al 2012), Paphiopedilum armeniacum (Zhang et al 2015), Bulbophyllum nipondhii (Pakum et al 2016), Paphiopedilum insigne (Diengdoh et al 2017), Anoectochilus elatus (Sherif et al 2018), Epipactis flava (Kunakhonnuruk et al 2018(Kunakhonnuruk et al , 2019 and Phalaenopsis amboinensis (Utami and Hariyanto 2019). We cultured the seed capsules of C. whiteae on different culture media and found that seeds of this species can germinate and grow successfully on MS media supplemented with 0.2 mg l −1 BAP.…”
Section: In Vitro Propagation and Assisted Translocationmentioning
confidence: 99%